The value of fractional exhaled nitric oxide in occupational diseases – a systematic review - Oțelea, Marina Ruxandra; Fell, Anne Kristin M.; Handra, Claudia Mariana; Holm, Mathias; Filon, Francesca Larese; Mijakoski, Dragan; Minov, Jordan; Mutu, Andreea; Stephanou, Euripides; Stokholm, Zara Ann; Stoleski, Sasho; Schlünssen, Vivi (Springer Science and Business Media LLC, 2022)
Fractional exhaled nitric oxide (FeNO) is a non-invasive biomarker of respiratory tract inflammation, originally designated to identify eosinophilic airway inflammation and to predict steroid response. The main field of application of this biomarker is asthma, but FeNO has also been used for other allergic and non-allergic pulmonary disorders such as chronic obstructive pulmonary disease, hypersensitivity pneumonitis and interstitial lung disease. A substantial part of respiratory diseases are related to work, and FeNO, a safe and easy measure to conduct, is a potential valid examination in an occupational setting.This systematic review assesses the value of measuring FeNO related to three types of airborne exposures: allergens, irritants, and respiratory particles inhaled during occupational activities. The review covers results from longitudinal and observational clinical studies, and highlights the added value of this biomarker in monitoring effects of exposure and in the diagnostic criteria of occupational diseases. This review also covers the possible significance of FeNO as an indicator of the efficacy of interventions to prevent work-related respiratory diseases.Initially, 246 articles were identified in PUBMED and SCOPUS. Duplicates and articles which covered results from the general population, symptoms (not disease) related to work, non-occupational diseases, and case reports were excluded. Finally, 39 articles contributed to this review, which led to the following conclusions:a) For occupational asthma there is no consensus on the significant value of FeNO for diagnosis, or on the magnitude of change needed after specific inhalation test or occupational exposure at the workplace. There is some consensus for the optimal time to measure FeNO after exposure, mainly after 24 h, and FeNO proved to be more sensitive than spirometry in measuring the result of an intervention. b) For other occupational obstructive respiratory diseases, current data suggests performing the measurement after the work shift. c) For interstitial lung disease, the evaluation of the alveolar component of NO is probably the most suitable.
Keywords: Fractional exhaled nitric oxide (FeNO); Occupational asthma; Occupational bronchitis; Occupational interstitial lung disease; Occupational hypersensitivity pneumonitis